Pinkalicious and the pinkamazing little library - Kann, Victoria (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2023)
"Pinkalicious reads in bed, at the table, and even while she is walking. When Pinkalicious can't find any new books to read at the library, what does she do? She makes a pinkamazing little library. It's booktastic"--
Ages 4-8.
Guided reading level J.
Keywords: Pinkalicious -- (Fictitious character) -- Juvenile fiction; Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Readers (Primary); Books and reading -- Fiction; Libraries -- Fiction; Readers (Publications)